ANALISIS FAKTOR MINIMNYA MINAT MEMBACA SISWA DI KELAS VI SDIT DAARUL ISTIQLAL KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - Aulia Fahma Balqis; Ema Rizky Ananda; Rora Rizky Wanindi; Wirda Shofia (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This research is motivated by the lack of interest in reading elementary school students, especially at SDIT DarulIstiqlal. This study aims to find out what factors cause the lack of interest in reading in students in class VI SDIT DaarulIstiqlal, to find out the role of teachers to increase reading interest in class VI students at SDIT DaarulIstiqlal and to know the role of parents to increase reading interest in students VI. SDIT DaarulIstiqlal, class VI SDIT DarulIstiqlal, Patumbak District, Deli Serdang Regency. This research is descriptive research. The subjects of the study were sixth grade students, teachers and parents of students. Data collection techniques using observation, interviews, and questionnaires. The data analysis technique used descriptive qualitative. The results showed that the internal factors that caused the low reading interest of the sixth graders of SDIT DarulIstiqlalPatumbak were reading skills and lack of reading habits. External factors that cause students' low interest in reading are a less supportive school environment, the role of the library is not maximized, limited books/reading materials, less supportive families, and the influence of watching television and using mobile phonesKeywords: Causing factor, Interest in reading, Research